The legal position of woman in Islamic law : A legal-philosophical perspective on sharia and human rights, with specific focus on child marriage and violence against women - Kalaja, Laura (My University, 2025)
This master’s thesis examines women within Islamic law, addressing the central research question: What is the legal position of woman in Islamic law? The analysis focuses on how Islamic primary legal sources define and regulate women’s roles in both public and private spheres, with particular attention to Sunni legal traditions. The study concentrates on the areas of marriage, including child marriage, and violence against women, as these domains involve fundamental issues of bodily integrity, agency, and autonomy. They also represent some of the most contested intersections between Islamic legal doctrine and international human rights norms. The motivation for this study arises from the legal injustices women encounter in societies influenced by Islamic law, as well as the universal significance of the topic, particularly in the context of Europe’s growing Muslim communities. The writer views that her research will contribute to legal scholarship by addressing a gap in the analysis of legal norms within Islamic law from both a normative legal and a philosophy of law perspective. It connects to contemporary discussions on human rights, legal pluralism, and gender studies. The theoretical framework incorporates legal-philosophical analysis, focusing on concepts of equality, justice, and the interplay between law and morality. The methodological approach relies on doctrinal legal analysis and legal linguistics to interpret key Islamic texts, supported by comparative insights from international human rights law. In the Scandinavian legal context, research on this topic remains limited, and discussions on Islamic law and its relation to human rights are often superficial. With the growing Muslim population, particularly in the Nordic countries, this thesis contributes to the discourse on legal pluralism, gender equality, and the role of Islamic law in contemporary legal systems. An analysis of women's legal status in Islamic law provides valuable perspectives for human rights discussions on Islamic law. Gender equality is a fundamental human rights issue, and the intersections of Islamic law and women’s rights represent crucial areas of study in advancing international human rights goals. This research will contribute to ongoing discussions about the compatibility of Islamic law with international human rights frameworks. The analysis reveals the complexity and contradictions in Islamic law’s legal foundations concerning gender differences, which stem from both divine authority and socio-political structures. Additionally, the challenges of reconciling Islamic law-based norms with universal human rights principles, particularly regarding women’s legal autonomy and equality will be attempted.
Keywords: Sharia, Islamic law, Women's rights, Human rights, Gender equality, Legal position, Legal pluralism